SARS-CoV-2 seroprevalence among people living with HIV in Guinea–Bissau. (August 2022) - Dutschke, A.; Wejse, C.; Nanque, J.P.; Medina, C.; Hønge, B.L.; Jespersen, S.; ,; Rodrigues, A.; da Silva, D.; da Silva, Z.; Medina, C.; Oliviera-Souto, I.; et al.
Abstract: Objectives: In low-income countries with poor SARS-CoV-2 monitoring and high HIV burden, the prevalence of SARS-CoV-2 is scarcely studied in people living with HIV (PLWH). We set out to measure SARS-CoV-2 seroprevalence in this group. Study design: Serosurvey of SARS-CoV-2 in PLWH. Methods: We measured IgG/IgM antibodies using point-of-care rapid tests in 294 PLWH with HIV-1, HIV-2 or HIV-1/2 dual infection at an HIV clinic in Guinea–Bissau between June 1, 2021, and October 1, 2021. Results: Unvaccinated PLWH ( n  = 195), constituting 66% of the total study population, had a seroprevalence of SARS-CoV-2 antibodies of 27.7%. Of SARS-CoV-2 seropositive unvaccinated PLWH, 71.2% reported no symptoms of COVID-19 since the start of the epidemic up to the inclusion date. Among all participants, 90.1% reported never having been tested for SARS-CoV-2 by any test ( n  = 292). Six participants reported a household death, corresponding to a crude annual death rate of 3.3 per 1000 people. Conclusions: Despite a low number of officially registered cases of SARS-CoV-2 in Bissau, we found a high seroprevalence of SARS-CoV-2 of 27.7% in unvaccinated PLWH. Coupled with few ever tested for SARS-CoV-2, it indicates that official PCR testing likely underestimates prevalence and that SARS-CoV-2 monitoring is challenged for PLWH. The low number of symptoms from seropositives may stem from survival bias, some effect of herd immunity or, coupled with a low crude annual death rate, that disease symptomatology and severity could be lower than expected.